PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS DENGAN DAYA INFORMASI AKUNTANSI SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marpaung, Hanna Hotmaidah Irene (Katalogis, 2014)
The  objectives  of  this  research  are  to  know  (1)  The  influence  of  corporate  socialresponsibility on profitability at manufacturing companies listed at Indonesian Stock Exchange (2) How Accounting Information Acts as a moderating variabel influencing the relationship between corporate social responsibility and profitability at manufacturing companies listed at Indonesian Stock Exchange. The sample on this research is manufacturing companies listed at Indonesian Stock Exchange in 2008-2012. Purposive sampling is a technique to judgment to found 8 (eight) companies. Independent variable on this research is profitability, dependen variable is corporate social responsibility, and moderating variable is Accounting Information Acts. The result shows (1) corporate social responsibility perform significant influencing on profitability at manufacturing companies listed at Indonesian Stock Exchange with value of t hitung > t table 3,077 > 2,024 (2) Accounting Information Act is unable to moderate the relationship between CSR and Profitability at manufacturing companies listed at Indonesian Stock Exchange with critical ration value of 0,124 at the level 0,05.